ANALISIS HUKUM ATAS KEKUATAN HUKUM GRANT SULTAN TERHADAP ADANYA PENERBITAN SERTIPIKAT OLEH PIHAK LAIN DILOKASI YANG SAMA - JOHN QADRI HANAFIAH (PREMISE LAW JURNAL, 2016)
The regulation on the position of rights in grant Sultan states that it is the Indonesian rights and is subject to the adat law. Grant Sultan in the Melayu kingdom was under the authority of Sultan. Therefore, grant Sultan which is issued for dependency was signed and stamped the Sultan of Melayu kingdom. The proving procedure of the grants before UUPA was in effective in the portions of land settled by the Melayunese under the four oeroengs was that they were issued, signed, and sealed by the head of oeroeng and then signed and sealerd them. After UUPA was in effective, the proving procedure was that the mechanism of its implementation was by direct conversion. The issuance of certificate in the grant has met the procedure of land registration according to PP (Government Regulation) No. 24/1997 which is done systematically. The Judge’s Verdict No. 96/Pdt/2012/PN-Mdn on the case of grant Sultan is legal because it is in accordance with article 32, paragraph 2 of PP No. 24/1997 on Land Registration. Keywords: Legal Protection, Grant Sultan, Certificate